FRI0537 Prevention strategy of osteoporotic fractures in portugal: an analyses on a cohort of hip fractured patients. (15th June 2017) - Daniel, A; Marques, ML; Brites, L; Torres, C; Marques, A; Silva, JA Pereira da
Abstract : Background: Despite the fact that Portugal has one of the lowest rates of hip fractures in Western Europe, more than 10.000 patients are admitted every year to the Portuguese National Health Service due to hip fragility fractures. The burden of the problem will tend to increase in coming years, unless effective preventive measures are put in place. 1 Objectives: The aim of our work was to evaluate the percentage of patients under osteoporotic treatment (OT) before and after a hip fracture (HF) and compare these results with the percentage of patients who should be under treatment, according to FRAX model and Portuguese cost-effectiveness guidelines (PG) for OT. 1 Methods: Patients diagnosed with a HF, between May 1st and October 31st 2013, from a single tertiary hospital, were included in this transversal study. Patients or their primary caregiver were contacted by phone to gather data regarding demographic and clinical features, including risk factors for Osteoporosis (OP) defined by FRAX®. Clinical data was obtained from medical files. FRAX® without mineral bone density was used to calculate the 10 year fracture risk. For each patient the FRAX® was scored according to data available the day before the present HF (ie the current fracture was not considered as a previous fracture for the purpose of risk prediction). Thresholds for therapeutic intervention were defined according to PG: a 10-year probability of a major osteoporotic fracture (OF) ≥11% and/or a 10 year probability of HF ≥3% 1 . Results: The mean age of the population (n=130) was 81.6±8.6 years, and 69.2% were female. Before the current HF, only 23 (17.7%) of the patients had been prescribed some form of medication for OP: bisphosphonates (n=2), strontium ranelate (n=3) and calcium + vitamin D supplementation (n=13); the other patients or caregivers didn't specify the ongoing medication. About 65 patients had a previous fracture, of which 8 patients had ≥1 fragility fracture of the hip; 6 had ≥1 symptomatic vertebral fragility fracture and 16 had ≥2 fragility fractures, independently of the site of the fracture. According to PG, all these 30 (26%) patients should be under OT without the need for FRAX® risk calculation. The mean 10-year major OF probability was 21.2±14% and the mean 10-year HF probability was 13.7±12.9%. According to FRAX®, 104 (80%) of the patients had indication to start OT based on the 10-year risk of major OF and 117 (90%) based on the 10-year risk of HF. After hospitalization, although all the patients had formal indication for treatment, only 11 (8.5%) patients had received a prescription for OT up to one year after the fracture event. Conclusions: Similar to other countries, the percentage of patients under OT (before and after HF) in Portugal is extremely low. Risk estimation by FRAX® and application of current PG would allow clinicians to identify these patients and introduce appropriate preventive measures. Continued efforts are needed to promote timely prevention, most especially after the first fragility fracture. References: Marques A, Rodrigues AM, Romeu JC et al. Multidisciplinary Portuguese recommendations on DXA request and indication to treat in the prevention of fragility fractures. Acta Reumatol Port 2016;41:305–321. Disclosure of Interest: None declared